Pengembangan Media Pembelajaran GALIH Berbasis Articulate Storyline untuk Meningkatkan Hasil Belajar pada Mata Pelajaran IPAS Kelas V - Hidayat, Wahyu; Junaedi, Akhmad (Universitas Muhammadiyah Magelang, 2026)
This study aims to develop a GALIH (Environmental Literacy Gallery) learning media based on Articulate Storyline that is feasible, practical, and effective in improving student learning outcomes in the subject of Science for grade V of SDN Sadeng 01. The study uses the Research and Development (R&D) method with the Borg and Gall development model modified into eight stages, including identification of potential and problems, data collection, product design, design validation, design revision, product trial, product revision, and usage trial. Data collection was carried out through test and non-test techniques, namely pretest and posttest, observation, interviews, and validation questionnaires and response questionnaires. Data analysis includes analysis of feasibility, practicality, and effectiveness of the media using percentage and N-gain calculations. The results showed that the GALIH media obtained a very high level of feasibility with a validation percentageof media experts of 90% and material experts of 93%. The practicality of the media is in the very practical category based on teacher responses (89%) and students (85%). The effectiveness of the media is shown through the N-gain value of 0.591 in small-scale trials and 0.604 in large-scale trials which are in the moderate category with an interpretation of being quite effective. Thus, the GALIH learning media based on Articulate Storyline is declared feasible, practical, and quite effective for use in science learning and contributes to improving the learning outcomes of fifth-grade elementary school students.